Aspire, Adapt, Anchor - Chi Jin (A+BE: Architecture and the Built Environment)
Human Creative Capital has become a key driver of urban competitiveness in the knowledge economy. However, metropolitan areas worldwide are experiencing diminishing appeal to young talents, with both high housing prices and poor housing quality being key contributing factors. This study investigates the decision-making mechanisms underlying young talents’ intercity migration and housing choices in China’s first-tier cities. While previous research has largely relied on neoclassical economic theories assuming rational decision-making, this study employs behavioral economics (Prospect Theory), psychological framework (Theory of Planned Behavior), and sociological perspective (Bourdieu’s Practice Theory) to examine how human agency shapes migration and housing decisions under uncertainty. Through mixed methods combining surveys and interviews, the research explores four questions following an “Aspire—Adapt—Anchor” narrative, investigating why young talents are drawn to these cities, how they navigate the housing market, and what influences their housing purchase and long-term settlement decisions. The findings extend conventional economic models in three significant ways. First, beyond traditional economic factors, the aspiration for self-actualization emerges as a key driver attracting young talents to first-tier cities, mediated through distinct psychological mechanisms. Second, their housing pathways reflect the dynamic interaction between structural constraints and individual agency, with different combinations of habitus and capital leading to diverse housing strategies. Third, while these young talents are initially drawn to first-tier cities, they show heightened sensitivity to potential losses in career prospects and housing costs, with their settlement intentions significantly anchored by institutional endowments such as public sector employment and housing tenure. Current housing situations and future migration prospects mutually shape their decision-making in metropolitan areas. By illuminating these psychological mechanisms in young talents’ major life decisions, this research suggests that policy interventions targeting psychological factors may be more cost-effective than traditional infrastructure-based approaches in talent retention.